SIFAT FISIKA DAN KIMIAWI KOMPONEN ASAP CAIR TEMPURUNG KELAPA HASIL ADSORPSI PADA ARANG AKTIF - Syahraeni Kadir; Purnama Darmadji Darmadji; Chusnul Hidayat; Supriyadi Supriyadi (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
Characterization of physical and chemical properties of aroma compounds from liquid smoke is a challenge because there is no satisfactory method of separation due to compound contributors generally present in a matrix at very low concentrations. This study aimed to separate and identify the components of "strong and pungent" liquid smoke aromatic compounds by adsorption using activated carbon method. The observed variables analyzed using GC-MS including yield, phenol, carbonyl, titration acidity and chemical compound profiles. The chemical components of liquid smoke found on the analysis by GC-MS were further analyzed using a molecular mechanics software to determine the polarizability, hydrophobicity and dwipol moment of each compound     in the liquid smoke fraction adsorption results. The analysis of variance (ANOVA) with SPSS software version 16, followed by Duncan Multiple Range Test at the level of 1% was employed especially for the yield of liquid smoke adsorption. The physico-chemical characteristics of  25 fractions of liquid smoke resulted from adsorption on activated carbon at pH 2-6 comprising of 0.53 to 3.89% phenolic; 1.09 to 2.59% carbonyl; 7.17 to 10.75% acidicity; and pH range from     2.39 to 2.91 with the color spectrum in the range of 308-415 nm. The results of the analysis using the molecular mechanics methods showed that the higher the value of polarizability and dipole moment of a compound, the more polar the compound. It is concluded that the removal of the "strong and pungent" aroma compounds on coconut shell liquid smoke in order to produce a mild scent (soft) can be performed by activated carbon adsorption method despite the results were not optimal yet. A polar adsorbent such as zeolite is requiredin the adsorption method for the removal of "strong and pungent” aroma compounds on liquid smoke